Characterization of transcription factor AP-2 beta mutations involved in familial isolated patent ductus arteriosus suggests haploinsufficiency - Ji, W; Benson, M; Bhattacharya, S; Chen, Y; Hu, J; Li, F (Academic Press Inc., 2014)
Background Patent ductus arteriosus (PDA) is one of the most common congenital heart defects. Transcription factor AP-2 beta (TFAP2B) mutations are associated with the Char syndrome, a disorder associated with PDA, and with facial and fingers abnormalities. Recently, we identified two TFAP2B mutations in two families without Char syndrome phenotype, c.601+5G>A and c.435-438delCCGG, and these TFAP2B mutations were associated with familial isolated PDA. The aim of this study was to identify the effects of these mutations on TFAP2B function. Methods Plasmids containing the wild-type or mutated TFAP2B were constructed and transfected in cells. Plasmids containing the TFAP2B coactivator, Cpb/p300-interacting transactivator 2 (CITED2), was also transfected. TFAP2B expression was detected by luciferase expression and by Western blot analysis. Results These mutations resulted in loss of transactivation function, which could not be improved by Cpb/p300-interacting transactivator 2. The c.601+5G>A mutated gene did not express any protein, whereas the c.435-438delCCGG mutation did not impact the transactivation function activated by the wild-type TFAP2B. Conclusions These results suggest that a haploinsufficiency effect of TFAP2B could be involved in familial isolated PDA. © 2014 Elsevier Inc. All rights reserved.